Ecosystem services and livelihoods in a changing climate: Understanding local adaptations in the Upper Koshi, Nepal - Bhatta, L.D.; Oort, Pepijn A.J. van; Stork, N.E.; Baral, H. (Informa UK Limited, 2015)
Mountain ecosystems are increasingly being affected by global environmental change, challenging the ubiquitous agro-ecosystem-based livelihoods of the people. This article uses participatory research methods to document and analyse (1) local and regional impacts of climate change on ecosystem services (ES) and livelihoods, and (2) the main current adaptation strategies of local peoples in the mountains of central Nepal. Major observed impacts include reduced precipitation and an irregular rainfall pattern, affecting paddy cultivation and winter crop production. Production is also affected by increased pest and pathogen prevalence. Other impacts include increased livestock disease and reduced forest regeneration. Our results confirm earlier findings of a decrease in the district’s forest cover in past; however, substantial efforts in forest conservation and management at the local level have gradually increased forest cover in recent years. Despite the increased potential for forest ecosystem services, the availability of forest goods, in particular fuel wood, fodder and litter, have decreased because of a strict regulation on forest goods extraction. Additionally, new invasive species are colonising these forests, preventing regeneration of preferred and local forest vegetation in some areas and, as a result, the densities of tree crops are changing. Most users cope with these changes by short term, reactive solutions. However, a number of local adaptation strategies, such as changing both agricultural practices and water harvesting and management, are increasing efficiency in resource use. To increase the adaptive capacity of poor households, we suggest it is essential to incorporate climate change adaptations within the local planning process.